Improving the Students’ Speaking Skill through Debate Technique - Firmansyah, Dody; Valatansa vegian, Else Elvisca (IKIP Siliwangi, 2019)
AbstractSpeaking is the highest target in English language because speaking is basis of communication which becomes a function learning. There are many kinds of technique to improve speaking skill and one of them is debate Technique. Therefore, the researcher wanted to find out whether or not debate technique can improve the students’ speaking skill and to analyze the classroom situation when debate technique is implemented in speaking class. This research used Collaborative Classroom Action Research and composed for two cycle then it practical and evaluated to categorize all facts including the success and the failure of the action. It means that the action should be stopped or continued and revised to the next cycle based on the selected criteria of success.The application of debate technique in teaching speaking at the first year of SMK Fajar Kencana was accompanied in two cycles including cycle one and cycle two. The members of this study were 29 students in class X AP. This is confirmed by students’ test score that upgraded in every cycle. In the cycle 1, the students’ got score of pre-test was 64,28. After the implementation of , the students’ speaking score were getting better.It can be seen from the result of students’avarage score cycle 1 was 67 and cycle 2 was 78.5. Debate is an appropriate technique used to improve students’ speaking skill for the students at SMK Fajar Kencana class X AP. It can be concluded that debate technique can improve students’ speaking interest and debate technique can improve speaking classroom into a better situation.